STUDY ON SPERM AGGLUTINATION WITH CHARACTERIZATION OF PLASMACOLLECTED FROM EPIDIDYMIS AND EJACULATE IN RAM - Haviz, Muhammad; Boediono, Arief; Agus Setiadi, M; Agungpriyono, Srihadi; Fahrudin, Mokhamad (Jurnal Veteriner; Vol 9 No 4 (2008), 2008)
This study was designed to optimalize the use of epididymal or ejaculate sperm and plasma for in vitro fertilization, that sperm agglutination was found at preparation. The rate of sperm agglutination was calculated the head-to-head sperm agglutination that were incubated in Krebs Ringer-(N-(2hydroxyethyl)piperazine-N’-(2-ethenesulfonic acid) or KR-HEPES medium in 38.50C with 5% CO2 at 1, 3, 5 and 7 hours culture in vitro. The rate of head-to-head sperm agglutination were decreased with time treatments. The cauda of sperm agglutination was lower than that caput, corpus epididymal and ejaculate sperm with statistically significant (P<0.01). These result reflected that distribution of anti-agglutinin might be higher in cauda epididymal than that other areas. Number of protein were characterize with SDS-PAGE as follow 11 bands in caput epididymal, 9 bands in corpus epididymal, 2 bands in cauda epididymal and 4 bands in seminal plasma. The higher distribution of protein was found at range 25-40 kDa in epididymal plasma of ram. However, further investigation should be conducted to determine presumptive anti-agglutinin by advance method.
Keywords: head-to-head sperm agglutination, cauda epididymal plasma